Metastatic pancreatic cancer now in remission: a case report and literature review - Charles W. Shi; Thomas J. VanderMeer; Anita Pudusseri (Discover Oncology)
Abstract Pancreatic cancer is a highly aggressive malignancy with the majority of patients presenting at a late stage with unresectable or metastatic disease. Even with first line treatment, median survival is approximately 11 months in patients with advanced PDAC. This report details the unique case of a patient that presented with peritoneal metastases from an adenocarcinoma of the body of the pancreas, had a remarkable response to palliative chemotherapy and is alive without evidence of disease 12 months following cessation of all active treatment. The initial diagnosis was 4 years ago and extensive resection of the primary was completed 2 years ago. The patient was started on standard FOLFIRINOX chemotherapy regimen, completed 6 cycles, but stopped Oxaliplatin and Irinotecan due to neuropathy and fatigue, on November 5, 2020, and transitioned to 5-fluorouracil (5-FU) and leucovorin. There was radiographic response and a notable decrease in tumor marker CA 19-9. On July 12, 2022 he underwent a multivisceral resection that included a radical anterograde modular pancreatico-splenectomy, partial gastrectomy, and splenic flexure colectomy with primary anastomosis due to tumor involvement of the posterior stomach and splenic flexure. Surgical pathology noted a moderately differentiated, grade 2 tumor staged ypT2 N0 M0. He continued the same adjuvant regimen of 5-FU and leucovorin for approximately 9 months with no new or recurrent disease on imaging. His CA 19-9 decreased within normal range after surgery and has remained within the normal limits. He remains on active surveillance. Overall, barring clear availability for targeted therapies, a metastatic PDAC of the tail may be considered to have a better prognosis than previously considered. FOLFIRINOX is the ideal treatment if the patient has a high-performance status, and PRODIGE 35 recommends 8 minimum cycles. However, in our case, the patient only tolerated 6 cycles and was still highly responsive. Despite a stage IV diagnosis, the primary tumor was resected in order to mitigate the risk for mutation and progression. Although rare, greater hope for patients with PDAC of the tail with favorable tumor biology responsive to FOLFIRINOX may contribute to increased surgical resection rates and improve survival rates.